Stakeholders’ perception on critical cost variation factors in Malaysian building projects - Sohu, Samiullah; Abdullah, Abd Halid; Nagapan, Sasitharan; Ali Buriro, Ahsan; Kaleemullah, K. (C.E.J, 2018)
Effective cost management is one of the prime requirements for successful completion of construction projects. However, deviation from initially planned cost had been prevalent in construction projects. Cost variation has become a frequent phenomenon in construction projects and Malaysian building projects has no exclusion. This paper aims to establish the critical factors instigating cost variation in Malaysian building projects. Extensive literature review and field survey were two main methods for conducting this study. 34 factors causing cost variation were identified through deep literature review. A questionnaire survey based on identified factors, was carried out among construction stakeholders: clients, consultants and contractors involved in handling of building projects in Malaysia. The collected data was analyzed using SPSS V22 software, which enabled the ranking of factors based on their Mean Value. The results of the survey indicated that (1) fluctuation in cost of materials, (2) improper planning, (3) Incompetent main contractors, (4) poor site management, (5) and client financial problems were top five critical factors causing cost variation in building projects. The inferences drawn in this study can serve as a guide lines for construction stakeholders to achieve effective cost management in building projects.